Intensity characteristics of the Latvian voiceless fricatives - Indričāne, Inese (Baltistica, 2014)
In the present research the intensity of the prevocalic voiceless fricatives of the Standard Latvian in the context of vowels [i], [iː], [ɑ], [ɑː], [u], [uː] has been investigated. The aim of this study is to compare results obtained for each voiceless fricative of the Standard Latvian by different approaches to intensity measurements (obtaining the intensity values of 1) spectral peaks; 2) overall intensity in the selection of 40 ms; 3) relative intensity).There are four voiceless fricatives in the Standard Latvian: labiodental /f/, dental /s/, alveolar /ʃ/ and velar /x/. The place of articulation of fricative /x/ varies from velar in the context of back vowels to palatovelar or palatal in the context of front vowels.The results are based on the analysis of speech data provided by 5 speakers of the Standard Latvian (men at the age between 19 and 39) having no speech disorders in their pronunciation. The analysed material consists of isolated symmetrical /CVC/ syllables, e. g., sis [sis], sīs [siːs], sas [sɑs], sās [sɑːs], sus [sus], sūs [suːs]. Each syllable was pronounced 3 times by each speaker. The total number of analysed speech units is 320.Data processing was performed using the software Wave Pad 5.40 (NHC Software, Inc.), Audacity 2.0.3 (SourceForge.net, AudacityTeam.org), Multi Speech 3700 (Kay Pentax), Praat 5.3.55 (Paul Boersma and David Weenink), SPSS 16 (IBM Corporation, Inc.) and MS Excel 10 (Microsoft Corporation).The intensity of spectral peaks for each voiceless fricative of the Standard Latvian was determined using FFT spectra obtained by software Multi Speech 3700. All FFT spectra were obtained from 40 ms interval selected approximately in the middle part of voiceless fricative. The intensity value was determined for the highest peak in the FFT spectrum corresponding to the maximum of energy in the frequency range 0–10 000 Hz. Using software Praat 5.3.55 overall intensity for the same 40 ms selection for each voiceless fricative of the Standard Latvian was obtained. Overall intensity in the selection of 40 ms was measured also in the middle part or steady state of the following vowel. According to these data, mean value (VSV), standard deviation (SN) as well as minimal (Min.) and maximal (Maks.) value was calculated for peak intensity (table 1-2, column I) and overall intensity in the 40 ms selection (for voiceless fricatives: table 1-2, column II; for following vowels: table 1-2, column III). The term relative intensity (table 1-2, column IV) in the present research is refered to the ratio between the mean value of overall intensity of voiceless fricative and following vowel.  Comparing three approaches used to determine intensity of voiceless fricatives, more consequent results are obtained by measuring overall intensity in the 40 ms selection and relative intensity. However, only relative intensity presents the most objective characteristics of the voiceless fricatives of the Standard Latvian since this approach takes into account not only properties of voiceless fricatives and influence of phonetic context but also several conditions related to the recording process (e. g., variations in loudness of voice or different recording level). According to the mean value of overall intensity and the value of relative intensity it is possible to separate voiceless sibilants [s], [ʃ] from voiceless non-sibilants [f], [x] in the context of all vowels, whereas the mean value of intensity obtained for spectral peaks of the voiceless non-sibilant [x] in the context of rounded vowels [u], [uː] overlap with the corresponding mean value of both voiceless sibilants.
Keywords: Latvian; acoustic phonetics; voiceless fricatives; sibilants; non-sibilants; intensity